Application of the NORIE-LACER-LOPP model for estimating the life cycle of glazed ceramic tiles under abrasion - Abitante, Ana Luiza Raabe (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
The aim of this paper is to discuss the application of the NORIE-LACER-LOPP model, which estimates the life cycle of glazed ceramic tiles submitted to abrasion caused by people’s traffic in free movement. The model indicates that the variation of aspect due to people’s traffic is proportional, respectively, to the square root of the time, which is given in minutes, and the square root of the traffic, which is given in millions of people. Considering the need to apply the model to any severity level, a study that defines the influence of the load and the concentration of abrasive on the acceleration factor was undertaken. Then, the prediction of the behaviour of four groups of ceramic tiles at different severity conditions was carried out. Finally, this paper presents the application of the model to any kind of ceramic tiles, considering the standard environment and also other severity levels.